Antimicrobial activity of organometallic isonicotinyl and pyrazinyl ferrocenyl-derived complexes. Issue 30 (17th July 2017) - Stringer, Tameryn; Seldon, Ronnett; Liu, Nicole; Warner, Digby F.; Tam, Christina; Cheng, Luisa W.; Land, Kirkwood M.; Smith, Peter J.; Chibale, Kelly; Smith, Gregory S.
Abstract : Isonicotinyl and pyrazinyl ferrocenyl-derived complexes were evaluated in vitro for antimycobacterial and antiparasitic activity. Abstract : Isonicotinyl and pyrazinyl ferrocenyl-derived complexes were prepared using various hydrazides and ferrocenyl aldehydes. Three heterobimetallic complexes were also synthesized from the Schiff base-derived isonicotinyl ferrocene complex using various platinum group metal dimers based on ruthenium, rhodium and iridium. All complexes were evaluated in vitro for antimycobacterial and antiparasitic activity. Against Mycobacterium tuberculosis H37Rv, the platinum group metal complexes showed glycerol-dependent antimycobacterial activity. The antiplasmodial activities against the NF54 chloroquine-sensitive strain of Plasmodium falciparum of some compounds were moderate, while some complexes also showed promising activity against Trichomonas vaginalis . Incorporation of the ferrocenyl-salicylaldimine moiety resulted in enhanced antimicrobial activity compared to the non-ferrocenyl compound in some cases. The bimetallic iridium-ferrocene isonicotinyl complex exhibited superior antitrichomonal activity relative to its organic counterpart, isoniazid. Furthermore, all these compounds, when screened on several normal flora bacteria of humans, showed no effect on the microbiome, emphasizing the selection of these compounds for these pathogens. The promising antimicrobial activities of the complexes thus supports incorporation of ferrocene as part of existing antimicrobial therapies in order to alter their biological activities favorably.